Fenomena "War Takjil" di Media Sosial pada Ramadan 1445 H (Toleransi dan Dampaknya) - Sumanti, Elvi; Sazali, Hasan (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2024)
This article discusses the phenomenon of "War Takjil" (iftar hunting) during the holy month of Ramadan 1445 H which went viral on social media. The "War Takjil" or the war over iftar food is not only an economic competition between food traders who sell various snacks and refreshing drinks to break the fast but also the phenomenon of non-Muslim communities taking part in fighting for iftar food like Muslims. This paper aims to see the extent of the impact of the "War Takjil" phenomenon by non-Muslims in Ramadan 2024, both on religious harmony, especially Muslims and non-Muslims, as well as its socio-economic impact and impact on Muslims. In addition to the impact caused, there are several messages that emerge from the phenomenon, both positive and negative. This paper uses a qualitative research methodology with an ethnographic approach. The analysis was carried out by observing and documenting certain groups (social media users, especially big cities in Java). The data was collected through capturing conversations of netizens on social media. "War Takjil" is a phenomenon when non-Muslims performs solidarity and social concern for Muslims. This reflects the values of togetherness and empathy in society.